An indication of current views of Australian general practitioners towards chiropractic and osteopathy: a cross-sectional study. Issue 1 (December 2016) - Engel, Roger; Beirman, Robyn; Grace, Sandra
Abstract Background While the role of complementary medicine therapies such as chiropractic and osteopathy is yet to be clearly delineated in the Australian context, demand for these services remains high. The attitudes of general practitioners towards chiropractors and osteopaths may have played a part in producing this outcome. However, this view is based on data that were more than 10 years old. Current anecdotal evidence suggests that the previous level of support may be declining in sections of the Australian medical profession. An assessment of the current views of general practitioners towards chiropractors and osteopaths is called for. The results being reported here represent the first stage of this assessment. Methods This cross-sectional study was designed as a quantitative descriptive study using an anonymous online survey that included closed and open-ended questions with opportunities provided for free text. The target population was Australian general practitioners. Inclusion criteria included current medical registration, membership of the Royal Australian College of General Practitioners and currently practicing as a general practitioner in Australia. The data being reported here were collected between May and December, 2014. Results There were 630 respondents to the online survey during this period representing a response rate of 2.6 %. Results were not uniform for the two professions. More general practitioners believed chiropractic education was not evidence-based compared to osteopathic education (70 % and 50 % respectively) while scope of practice was viewed as similar for both professions. A majority of general practitioners had never referred a patient to either profession (chiropractic: 60 %; osteopathy: 66 %) with approximately two-thirds not interested in learning more about their education (chiropractors: 68 %; osteopaths: 63 %). Conclusions This study provides an indication of the current views of Australian general practitioners towards chiropractors and osteopaths. The findings suggest that attitudes may have become less favourable with a growing intolerance towards both professions. If confirmed, this has the potential to impact health service provision. The results from this cross-sectional study suggest that obtaining representative general practitioner views using online surveys is difficult and another approach is needed to supplement or replace the current recruitment strategy.'